METONYMIC EXPRESSIONS IN TRUYEN KIEU BY NGUYEN DU AND ITS ENGLISH EQUIVALENTS - Lê Thị Hà Ny (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to examine the metonymic expressions (MEs) in Nguyen Du‟s Truyen Kieu and their equivalents in English by Michael Counsell. Specifically, this thesis was carried out to investigate the commonly translation procedures used to convey the content and meaning of MEs from Vietnamese into English. 184 samples related to these MEs in Vietnamese as well as their equivalents in the translational version were collected from the book to support the investigation. Both qualitative and quantitative approaches were applied in order to help the researcher achieve the aims and objectives proposed. Furthermore, after studying the finding of the thesis, it was discovered that the translator employed many different procedures of translating suggested by Peter Newmark to translate these MEs from Vietnamese into English. Finally, I hope that the results of the study could provide teachers and learners of English and Vietnamese with a better understanding of translation procedures from Vietnamese into English in terms of MEs, and giving some suggestions for further research and implications for language teaching and learning as well.